Optimising protein synthesis in cell‐free systems, a review. Issue 1 (21st February 2021) - Batista, Angelo C.; Soudier, Paul; Kushwaha, Manish; Faulon, Jean‐Loup
Abstract: Over the last decades, cell‐free systems have been extensively used for in vitro protein expression. A vast range of protocols and cellular sources varying from prokaryotes and eukaryotes are now available for cell‐free technology. However, exploiting the maximum capacity of cell free systems is not achieved by using traditional protocols. Here, what are the strategies and choices one can apply to optimise cell‐free protein synthesis have been reviewed. These strategies provide robust and informative improvements regarding transcription, translation and protein folding which can later be used for the establishment of individual best cell‐free reactions per lysate batch.